1975
DOI: 10.1007/bf00562315
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of fixed interval and visual analogue scales for rating chronic pain

Abstract: A visual analogue scale (VAS) and a 4-point scale (FPS) have been compared in patients suffering from prolonged constant pain due to chronic inflammatory or degenerative arthropathy. Each patient was treated with a constant low or high dose of paracetamol or dihydrocodeine throughout a four week period. The VAS was accurate, as reliable and more sensitive than the FPS in registering the intensity of chronic pain. Separate records of each estimate, sealed immediately on completion by the patient, resulted in om… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
233
1
7

Year Published

1981
1981
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 449 publications
(242 citation statements)
references
References 6 publications
1
233
1
7
Order By: Relevance
“…This lower level of responsivity may be related to the lower number of response categories of these measures. However, we did find that both of these scales were able to detect changes in pain associated with differences in water temperature, indicating that they are valid and could be used when responsivity is not a critical issue [6,9,24,25,31]. Also, statisticians note that it is possible to draw valid conclusions using parametric analysis with ordinal data, such as data from VRSs, especially if number of categories in the scale is 5 or more [5,18,38].…”
Section: Discussionmentioning
confidence: 99%
“…This lower level of responsivity may be related to the lower number of response categories of these measures. However, we did find that both of these scales were able to detect changes in pain associated with differences in water temperature, indicating that they are valid and could be used when responsivity is not a critical issue [6,9,24,25,31]. Also, statisticians note that it is possible to draw valid conclusions using parametric analysis with ordinal data, such as data from VRSs, especially if number of categories in the scale is 5 or more [5,18,38].…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Although the VAS may show deficiencies regarding understanding (especially related to old age) and precision, 10,11 it provides a validated and meaningful measure of anaesthetic efficiency, 12 being used for this purpose by many authors. 2,12,13,14,15 This investigation not only ratified the results obtained by the mentioned authors 2,5,7 with respect to anaesthetic efficiency, but also showed that there were no differences between the solutions with respect to palatal pain sensitivity to injection five minutes after infiltration at the buccal side, which could be seen from the values of 2.3 and 2.7 for VAS, respectively for articaine and lignocaine.…”
Section: Discussionmentioning
confidence: 99%
“…Rating scales have been shown to outperform other utility measures in differentiating among alternative health states (22)(23)(24). Although ratings are not used as a measure under conditions of uncertainty, other investigators have reported them to be a reliable and consistent method for assessment of quality of life, noting that rating-scale values tend to be lower than those elicited by the standard gamble and other utility measures (25)(26)(27)(28)(29)(30)(31)(32)(33). In a study of patients with chronic musculoskeletal pain, a rating scale was preferred to a standard gamble instrument as a means of assessing the impact of interventions on health outcomes, because it had better construct validity and ability to detect differences in health status (33).…”
Section: Discussionmentioning
confidence: 99%